Measurement invariance of the Personality Inventory for DSM-5 across sex - Rivard, Geneviève; Le Corff, Yann; Lapalme, Mélanie; Forget, Karine (Frontiers in Psychiatry, 2024)
There has been an international movement towards dimensional models of personality disorders (PDs) in the last decades, which culminated in the publication of the Alternative Model of Personality Disorders (AMPD) in the Emerging Measures and Models section of the DSM-5 (American Psychiatric Association, 2013). This model was accompanied by a APA-sanctioned Personality Inventory for DSM-5 (PID-5;Krueger et al., 2012) for the assessment of the AMPD pathological personality traits. One major issue with the assessment of personality disorders pertains to sex differences (Paggeot & Huprich, 2018), and measurement invariance across sex in assessment instruments for PDs is necessary in order to ensure non-biased evaluations and to make valid comparisons between men and women. This study aimed to provide more information on measurement invariance across sex for the PID-5, using both the original scoring approach provided by the authors of the instrument and the scoring approach suggested by the APA in the published version of the PID-5. This study was conducted with a sample of 2273 participants from the general Québec (Canada) adult population aged 18 to 90 years (M = 46.59; SD = 16.32; 51.8% women). Results showed that both models have good fit to the data and that they are both fully invariant across sex (i.e. strict invariance). The APA scoring approach showed better fit to the data and appears to attenuate the cross-loading problem observed with the original scoring approach. In light of these results, we recommend using the APA scoring approach to derive domain scores.